Penerapan Media Pembelajaran Berbasis Interacty untuk Meningkatkan Daya Ingat Siswa pada Mata Pelajaran Sejarah di SMK Model Patriot Iv Ciawigebang (Indo-MathEdu Intellectuals Journal, 2026)
The low level of students' memory of History material is one of the obstacles in the learning process at SMK Model Patriot IV Ciawigebang. One effort that can be done to overcome this problem is to utilize Interacty-based learning media that presents material interactively so as to increase student involvement in learning. This study aims to analyze the effect of implementing Interacty-based learning media on improving students' memory in History subjects. The study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of students of class XI TJKT 1 as the experimental class and XI TJKT 2 as the control class. Data were collected through pretest and posttest tests, then analyzed using prerequisite tests and independent samples t-test. The results showed that there was a significant difference between students' memory in the experimental class and the control class, as indicated by the t value = -7.260 with df = 60 and Sig. (2-tailed) = 0.000 (